2006
DOI: 10.1111/j.1075-122x.2006.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Compliance in a Breast Cancer Prevention Trial

Abstract: The impact of chemoprevention trials can be hampered by poor participant compliance with the study medication. We used medication monitoring systems and pill count data to try to establish factors that may predict compliance with the International Breast Intervention Study (IBIS) and whether the participants went on to complete or benefit the trial. Women who took their trial medication in a regular pattern rather than randomly were more likely to be of benefit to the study (p = 0.003). For those women who fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…Adherence data in smokers were obtained at 8 time points during the 36 months, showing a gradual decline in adequate adherence that became highly significant at 3 years. These smoking and adherence data are consistent with a small adherence substudy (n ¼ 100) of IBIS-1 (30) and with data from the NSABP STAR showing an association of smoking history with decreased adherence to either tamoxifen or raloxifene (31). Of interest, tamoxifen adverse events (e.g., depression and migraines) correlated with current smoking (vs. nonsmoking) in a separate study (32), and a previous study by Land and colleagues showed a strong association of smoking with an increased risk of breast cancer (P ¼ 0.007; ref.…”
Section: Healthy High Risk/preventionsupporting
confidence: 86%
“…Adherence data in smokers were obtained at 8 time points during the 36 months, showing a gradual decline in adequate adherence that became highly significant at 3 years. These smoking and adherence data are consistent with a small adherence substudy (n ¼ 100) of IBIS-1 (30) and with data from the NSABP STAR showing an association of smoking history with decreased adherence to either tamoxifen or raloxifene (31). Of interest, tamoxifen adverse events (e.g., depression and migraines) correlated with current smoking (vs. nonsmoking) in a separate study (32), and a previous study by Land and colleagues showed a strong association of smoking with an increased risk of breast cancer (P ¼ 0.007; ref.…”
Section: Healthy High Risk/preventionsupporting
confidence: 86%
“…3 The significant association between persistence with treatment and increasing numbers of prescribed medications has been observed in previous studies of tamoxifen persistence 13,14 and more recently in reports from the international breast intervention study, IBIS-I. 31 It has been suggested that patients with a large medication burden develop routines to promote adherence. 13,31 It is also possible that the healthy drug user effect 32 may play a role in this association, whereby patients with good health-seeking behavior who are in turn more likely to seek and receive medical treatment for conditions are also those patients with good medication-taking behavior.…”
Section: Discussionmentioning
confidence: 91%
“…31 It has been suggested that patients with a large medication burden develop routines to promote adherence. 13,31 It is also possible that the healthy drug user effect 32 may play a role in this association, whereby patients with good health-seeking behavior who are in turn more likely to seek and receive medical treatment for conditions are also those patients with good medication-taking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…problem, reaching rates as high as 60%, 20,23,24,[28][29][30][31][32] and places patients at risk of inadequate clinical benefit. [24][25][26][27]40,41 The primary goal of the present study was to evaluate the compliance of patients with breast cancer with hormonal therapy when treatment involved regular follow-up with a breast specialist. Although the literature remains scarce concerning the contribution of the required type of follow-up, the need to provide information to the patients remains crucial.…”
Section: Discussionmentioning
confidence: 99%